Observations on prostaglandins in normal and leukemic human lymphocytes - Carpentieri, Ugo; Brouhard, Ben H.; LaGrone, Lavenia; Lockhart, Lillian H. (Prostaglandins, 1980)
Prostaglandins E (PGE) and F 2α (PGF 2α) were measured in lymphocytes of normal subjects, children with acute lymphocytic leukemia (ALL), and adults with chronic lymphocytic leukemia (CLL). In ALL lymphocytes PGE increased from a normal value of 25 pgrams to 270 pgrams/10 6 cells, and PGF 2α increased from a normal value of 31 pgrams to 482 pgrams/10 6 cells. In CLL lymphocytes, levels of PGE and PGF 2α were normal or low. When normal lymphocytes were stimulated with phytohemagglutinin (PHA), the level of PGE and PGF 2α fluctuated, followed by corresponding changes in the level of cyclic nucleotides. In cultured ALL lymphocytes, the level of PGE remained high, while cyclic 3′:5′-adenosine monophosphate (c-AMP) level was constantly low, and the initial high level of PGF 2α fluctuated in relation to similar oscillations of cyclic 3′:5′-guanosine monophosphate (c-GMP). These values were lower, although not significantly, when ALL lymphocytes were stimulated with PHA. When CLL lymphocytes were stimulated with PHA, the level of PGE remained low (20 pgrams), as did that of c-AMP. The level of PGF 2α, after a brief initial increase (130 pgrams), returned to and remained at a lower level (60 pgrams) while the level of c-GMP was persistently high. These results suggest: (1) prostaglandins may indirectly influence the cell cycle, possibly through modulation of cyclase activity and levels of cyclic nucleotides; and (2) some derangement of this regulatory mechanism may be present in leukemic lymphocytes.